Allergic Rhinitis in Bangladesh: Unveiling the Tapestry of Patterns, Coping Strategies, Risk Factors and Impact on Daily Activities among Adult Population - A Cross-Sectional Study at a Tertiary Hospital (Central Medical College Journal, 2024)
Background: According to the research, despite the prevalence of allergic rhinitis (AR), it is frequently misdiagnosed or undertreated about its pattern, severity and risk factors. Aim: This study investigated the pattern, severity, and illness features of AR in Cumilla, Bangladesh, as well as symptom-relieving coping strategies among adult population. Methods: We conducted a quantitative observational descriptive cross-sectional study on outpatients from the ENT department of Central Medical College Cumilla, Bangladesh, between January 2020 and February 2023. Initially the sample size was 2949 and finally n= 2,549 participants selected who experienced at least one of the four symptoms of AR, namely runny nose, sneezing, nasal blockage, itchy nose, and watery eyes, unrelated to a cold or flu in the prior year. The study's results were the triggers, pattern, severity, categorization of AR (2016 ARIA criteria), and coping strategies. We did descriptive statistics, univariate analytic statistics, and binary analysis. At